Childhood Trauma and Personal Mastery: Their Influence on Emotional Reactivity to Everyday Events in a Community Sample of Middle-Aged Adults - Infurna, Frank J.; Rivers, Crystal T.; Reich, John; Zautra, Alex J. (PLOS ONE, 2015)
Childhood trauma is associated with premature declines in health in midlife and old age. Pathways that have been implicated, but less studied include social-emotional regulation, biological programming, and habitual patterns of thought and action. In this study we focused on childhood trauma’s influence via alterations in social-emotional regulation to everyday life events, a pathway that has been linked to subsequent health effects. Data from a 30-day daily diary of community residents who participated in a study of resilience in Midlife (n = 191, Mage = 54, SD = 7.50, 54% women) was used to examine whether self-reports of childhood trauma were associated with daily well-being, as well as reported and emotional reactivity to daily negative and positive events. Childhood trauma reports were associated with reporting lower overall levels of and greater variability in daily well-being. Childhood trauma was linked to greater reports of daily negative events, but not to positive events. Focusing on emotional reactivity to daily events, residents who reported higher levels of childhood trauma showed stronger decreases in well-being when experiencing negative events and also stronger increases in well-being with positive events. For those reporting childhood trauma, higher levels of mastery were associated with stronger decreases in well-being with negative events and stronger increases in well-being with positive events, suggesting that mastery increases sensitivity to daily negative and positive events. Our results suggest that childhood trauma may lead to poorer health in midlife through disturbances in the patterns of everyday life events and responses to those events. Further, our findings indicate that mastery may have a different meaning for those who experienced childhood trauma. We discuss social-emotional regulation as one pathway linking childhood trauma to health, and psychosocial resources to consider when building resilience-promoting interventions for mitigating the detrimental health effects of childhood trauma.